2020
DOI: 10.1016/j.triboint.2019.105949
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lubricant performance in punching and blanking

Abstract: Punching and blanking processes are characterized by severe tribological conditions due to the creation of virgin surfaces, which are highly prone to develop pick-up of workpiece material on the punch surface. Hazardous forming lubricants are, therefore, commonly used in punching and blanking processes for avoidance of wear induced process deviations such as diminished surface quality, reduced dimensional accuracy and reduced tool life. The present study characterizes the function and performance of lubricants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The experiments revealed that an applicable temperature range and a high load bearing capacity are central lubricant properties necessary for ensuring sufficient lubricating ability for punching and blanking operations. Additive package based on Ca-, P-, and S-additives was suggested to replace the hazardous chlorinated paraffins EP additive in mineral oils [341]. Wear particles generated due to the relative sliding of the roll and the sheet metal in the roll bite are one of the main factors that contaminate the surface of a cold rolled steel sheet.…”
Section: Wear In Metalworking and Polishing Processesmentioning
confidence: 99%
“…The experiments revealed that an applicable temperature range and a high load bearing capacity are central lubricant properties necessary for ensuring sufficient lubricating ability for punching and blanking operations. Additive package based on Ca-, P-, and S-additives was suggested to replace the hazardous chlorinated paraffins EP additive in mineral oils [341]. Wear particles generated due to the relative sliding of the roll and the sheet metal in the roll bite are one of the main factors that contaminate the surface of a cold rolled steel sheet.…”
Section: Wear In Metalworking and Polishing Processesmentioning
confidence: 99%
“…It was attractive since it can yield fully burnished surfaces in mass production. Under severe shearing conditions, the abrasive wear of the blanking punch became an issue [6]. When fine blanking ductile materials such as austenitic stainless steels or titanium alloys, the fine-blanking punch often suffered from adhesive wear, where the fresh work fragments and their oxide debris particles adhered onto the punch surfaces [7].…”
Section: Introductionmentioning
confidence: 99%